“An Eternal Alien”: South African Autobiographical Beginnings - Raditlhalo , Tlhalo Sam (Journal of Literary Studies, 2011)
This article examines South African autobiographical writings from the early to the middle twentieth century. A careful reading of these writings shows that the various ways in which the autobiographical subjects constructed their "South Africanness" was a result of the interplay between power, history, racism/placism and culture. These discourses are discussed in relation to how they affected the subjectivities of the authors and led to aspects of hybridisation, alienation and exile. The polyglot nature of South Africa is examined as part of the subtext of identity formation and fostering within the bounds of postcolonial/post-apartheid autobiographical possibilities as part of national identities. In conclusion, this article reflects on present-day autobiographical practice. Questions of how to wrest the practice from the stultifying theory and criticism of Western scholarship are posed in order to identify further research possibilities and, hopefully, an epistemological break in African autobiographical studies. A close reading of the texts of Roy Campbell and Bloke Modisane is therefore undertaken. The rise of a literate class played a significant role in ushering in autobiographical writings since literary beginnings gave a sense of permanence and fulfilment to these writers and led them to assume local and international identities which they experienced differently. A particular aspect that is examined is the cross-racial transcendence which some of the autobiographical subjects attained as a way of overcoming hybridity and ambivalence in South Africa, for example as is reflected in Helen Joseph's moving text Side by Side (1986). Opsomming Hierdie artikel ondersoek Suid-Afrikaanse outobiografiese geskrifte vanaf die vroee tot die laat twintigerjare. 'n Sorgvuldige ondersoek van hierdie geskrifte toon dat die verskillende maniere waarop die outobiograwe hul "Suid -Afrikaansheid" gekonstrueer het 'n gevolg was van die wisselwerking tussen mag, geskiedenis, rassisme/plasing en kultuur. Hierdie diskoerse word bespreek in terme van hoe dit die outeurs se subjektiwiteite beinvIoed het en gelei het tot aspekte van hibridisering, vervreemding en ballingskap. Die veeltalige aard van Suid-Afrika word ondersoek as deel van die subteks van identiteitsvorming en -bevordering binne die grense van die postkoloniale/post-apartheid outobiografiese praktyk. Vrae oor hoe die praktyk van die afstompende teorie en kritiek van Westerse vakkundigheid bevry kan word, word gevra ten einde verdere navorsingsmoontlikhede en hopelik 'n epistemologiese breuk in outobiografiese studies in Afrika te identifiseer. 'n Deurdringende studie van die tekste van Roy Campbell en Bloke Modisane word onderneem. Die opkoms van 'n geletterde klas het 'n belangrike rol gespeel in die inluiding van outobiografiese geskrifte aangesien dit hierdie skrywers 'n sin van permanensie en vervulling gegee het en daartoe gelei het dat hulle plaaslike en internasionale identiteite aangeneem het wat hulle verskillend ervaar het. 'n Besondere aspek wat ondersoek word is die kruiskulturele transendensie wat sommige van die outobiograwe bereik het as 'n manier om hibriditeit en ambivalensie in Suid-Afrika te oorbrug, byvoorbeeld soos weerspieel word in Helen Joseph se hartroerende teks Side by Side (1986).